Strategy Eradication Corruption Through Strengthening Legal Instruments - Mohd Yusuf Daeng; Zulkarnaini; M. Fadli Daeng Yusuf (CV. AFDIFAL MAJU BERKAH, 2022)
Corruption crime in Indonesia is widespread in society, its development continues to increase from year to year. This increase occurred both in the number of cases and in the number of state financial losses as well as in terms of quality which were increasingly systematic and in scope that entered all aspects of people's lives. As a result, the title as one of the most corrupt countries in the world has become an unavoidable harsh reality for our nation. The government has tried to fight corruption in various ways. For example, by strengthening existing legal instruments and creating an institution to eradicate corruption. The KPK as an independent institution that specifically handles corruption has become a real effort to prevent and take action against corruption. But on the other hand, enforcement efforts require a lot of money. Not to mention if it is calculated from the impact on the life of society and the state.